APPLICATION AND IMPACT OF ARTIFICIAL INTELLIGENCE IN MEDICAL CARE: A SYSTEMATIC REVIEW OF THE LITERATURE - Brito, Carla Maria Soares; Lopes, Lúcio Eugênio Cerqueira; Lira, Elton Jones Dias; Barros, Gullit Vinicius Silva; Pinheiro, Judimilla Almeida; Fortes, Marina Sampaio; Carvalho, João Lucas Gomes; Sousa, Iargo Franco Diogenes Urbano; Passos, Maysa Maria Portela Martins Brito; Bezerra, Luma de Alencar; Furtado, David Guerra; de Carvalho, Gabriel Guedes Farias (Seven Editora, 2025)
Until recently, the application of artificial intelligence (AI) in healthcare was a source of much speculation but little action. Defining AI as "a set of technologies that allow machines and computers to simulate human intelligence," clinical researchers often compare AI to human performance as a means of validation. The present study aims to analyze the application and impact of artificial intelligence in medical care. This systematic review was used to evaluate the applications and impacts of artificial intelligence in medical care. The guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses" (PRISMA) were followed. In addition, the PubMed, ACM Digital Library, IEEE Xplore, Web of Sciene, and ScienceDirect databases were used for literature review. The literature review revealed 7,415 articles in total. Of these, 11 articles were selected, 5 (45.46%) investigated the impact of AI in medicine, and 6 publications (54.54%) evaluated AI education in medicine. The current application of AI in medical education is focused on clinical specialized training and continuing education, with the main areas of application being radiology, diagnostics, surgery, cardiology, and dentistry. The primary role is to help doctors improve their efficiency and accuracy. The potential benefits of AI for diagnosis, treatment, and drug discovery generate optimism and hope for new knowledge and improved patient outcomes.DOI: https://doi.org/10.56238/sevened2024.037-123